2001
DOI: 10.1038/sj.ejcn.1601173
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of phytosterols in diacylglycerol versus triacylglycerol improves the serum cholesterol-lowering effect

Abstract: Objective: This study was performed to investigate the difference in the serum-cholesterol-and triglyceridelowering activities between phytosterols dissolved in diacylglycerol (PSaDG) and dispersed in triacylglycerol (PSaTG). The effects of the solvent on the concentrations of serum b-sitosterol and campesterol were examined. Design: The study had a randomised crossover design. Subjects: Twelve healthy normocholesterolemic or moderately hypercholesterolemic men aged 29 ± 50 y participated in this study. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…For instance, as shown in a human clinical study [29], oral supplementation of phytosterol dispersed in a diacylglycerol-rich oil increased the health benefits of phytosterols compared to a triacylglycerol oil. The authors explained that the reason for this could be that diacylglycerol-rich oil is a better solvent for hydrophobic components as phytosterols.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, as shown in a human clinical study [29], oral supplementation of phytosterol dispersed in a diacylglycerol-rich oil increased the health benefits of phytosterols compared to a triacylglycerol oil. The authors explained that the reason for this could be that diacylglycerol-rich oil is a better solvent for hydrophobic components as phytosterols.…”
Section: Discussionmentioning
confidence: 99%
“…However, this view has recently been challenged, since several published papers have shown that much lower concentrations of phytosterols have an effect, when administrated in a more suitable matrix (10,11). In earlier studies, phytosterols were administrated in a triglyceride matrix, which also is the matrix in most commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, phytosterols were administrated in a triglyceride matrix, which also is the matrix in most commercial products. However, when the phytosterols were administrated as components of a phospholipid or diacylglycerol mixture, cholesterol absorption, serum cholesterol level, and development of atherosclerotic plaques decreased significantly, also at intakes corresponding to the natural consumption or just moderately increased (10)(11)(12)(13). Furthermore, it was recently shown that selectively removing the phytosterols from wheat germ, which was used as a component in a test meal (phytosterol content in the control diet with phytosterols was 330 mg), causes a 40% increase in cholesterol absorption (12).…”
Section: Introductionmentioning
confidence: 99%
“…A este respecto, los esteroles de plantas son más eficientes cuando se mezclan con grasa que cuando se administran aislados (Pelletier et al, 1995), sin embargo estudios recientes sugieren que bastarían pequeñas proporciones de grasa (yogurt con 0,7% de grasa) para ser efectivos bajando los niveles de colesterol (Plat et al, 2000 b). También se ha encontrado que la solubilización en fosfolípidos (Ostlund et al, 1999), así como en diacilglicerol (Meguro et al, 2001) incrementa su biodisponibilidad. Después de su absorción, los fitosteroles se incorporan a lipoproteínas (Miettinen, 1980;Boberg et al, 1988) y pueden acumularse en el hígado y otros tejidos (Sugano et al, 1978;Boberg et al, 1986,), habiéndose sugerido que pueden ser precursores de hormonas esteroídicas (Subbiah y Kuksis, 1969 …”
Section: Absorción Intestinal De Los Fitosterolesunclassified